Towards a “more American America”: representations of Spanish America in didactic manuals for the formation of Argentinian teachers (1910-1913) (Práxis Educativa, 2013)
This paper aims to identify the representations of Spanish America in manuals for teachers’ formation, specially in Carlos Lamarca’s Compendio de la Historia General de América (1910-1913). The methodology used was the study of the events of American history present in each manual, in order to answer the following question: What are the representations of America in Argentinian manuals? The results indicate that Carlos Lamarca conceives America in two ways: before its independence, in which the continent is differentiated according to its geographical location; and after emancipation, with the deconstruction of the idea of America. Thus, by identifying the representations of the continent, it is possible to locate the social spaces in which they were written, enabling the understanding of their deeper meanings. Keywords: Spanish America. Representation. Didactic manual.